Features of the electrolyte distribution in various tissues in miniature pigs - A. V. Fatianova; V. A. Lavrinenko; O. V. Trapezov; N. S. Yudin (Вавиловский журнал генетики и селекции, 2017)
Striking similarities between human and miniature pig anatomy and physiology of the cardiovascular system, skin and digestive organs have made miniature pigs a successful animal model for addressing problems of xenotransplantation. However, despite the widespread interest in this breed of animals, the distribution of water and electrolytes in the tissues of miniature pigs remains poorly understood, which led us to conduct this study. The distribution of sodium, potassium cations and water in skeletal muscles, myocardium, smooth muscle elements of the vascular system, liver and skin of mini-pigs differing in gender and behavioral response to humans has been studied. Quantitative determination of sodium and potassium cations was performed by atomic absorption spectroscopy. It was shown that skeletal and smooth muscles differ in electrolyte content. The impact of behavioral response to humans on the electrolyte level in skeletal muscle was detected. The data are confirmed by two-factor dispersion analysis. The accumulation of water in muscle samples of “tame” males as compared with cowardly animals was shown. The impact of different behavioral types on the amount of sodium in the skin was revealed. The impact of the gender of animals or the type of behavior on the sodium level in the liver was not detected. However, a significant amount of potassium was found in the liver as compared with sodium level, which is possibly associated with a high density of cellular elements. The gender and behavioral type of animals did not have an impact on the distribution of potassium and the mass fraction of water in the skin and liver. Some differences in the distribution of the main extracellular and intracellular sectors’ cations were revealed, and so was the dependence of the electrolyte content on the functional characteristics of the tissues. The data obtained demonstrate that miniature pigs can be an informative animal model for  studying the influence of genetic (gender) and phenotypic (behavioral response) aspects on the parameters of water-electrolyte homeostasis.